THEME AND THEMATIC PROGRESSIONS IN ENGLISH CHILDREN'S SHORT STORIES - Faradhita Ajeng Erstiana, - (2018)
The present research analyzes the theme and thematic progressions of two selected children's short stories entitled Little Red Riding Hood by Brothers Grimm and The Ugly Duckling by Hans Christian Andersen. This study uses Halliday and Matthiessen's (2004) theory on Theme and Rheme and Daneš's (1974) and Paltridge's (2006) theory on Thematic Progression pattern. Descriptive qualitative method was employed to give detailed analysis on Theme and Thematic Progression of the stories. Some calculation was also performed to find out the percentage of data frequency to reinforce the findings and discussion. The analysis shows that there are three types of Theme included in the stories: topical theme, textual theme and interpersonal theme, and there are three types of Thematic Progression patterns used in the stories: linear theme, constant theme, and split rheme or multiple theme. This trend shows that messages of narrative text, including short story can be developed through the use of topical and textual theme, while the pattern of delivering the message of the story can be developed through the use of linear pattern theme because it creates a dynamic text that is more exciting for the readers, especially children.